Measuring and observation tool in sports (MOTS) V2.0 - Perea, A.; Castellano, J.; Alday, L. (World Congress of Performance Analysis of Sport VIII, 2008)
Users can define up to 24 mutually exclusive code sets and up to 288 different behaviours to facilitate data collection, and thus they can work with any observational data type: event sequences, event sequences over time, state sequences, interval sequences or multi-event sequences. MOTS plays digital video files, which allow video and taxonomic tools to be displayed on the screen at the same time. The observations are registered automatically including the time and the duration of the event, in frames and in seconds simultaneously. Furthermore, the data analysis feature allows the user to calculate the percentage of intervals, the frequency distributions and the conditional probabilities. The registered data are stored in Microsoft Excel worksheets and may also be exported to some statistics programs as for example SAS and SPSS.